Performance Prediction of the Catalyst PR-81 at the Production Unit Using Mathematical Modeling Method; Procedia Engineering; Vol. 113 : Oil and Gas Engineering (OGE-2015), Omsk, 25-30 April 2015 - Yakupova I. V. Inna Vagizovna; Chernyakova E. S. Ekaterina Sergeevna; Ivanchina E. D. Emilia Dmitrievna; Beliy A. S. Aleksandr Sergeevich; Smolikov M. D. Mikhail Dmitrievich (2015, 2015)
Title screen